Chekhov's corner: Using Dreamland: The True Tale of America's Opiate Epidemic in the public health classroom. (13th May 2019) - Basch, Corey H; Wagner, Victoria H
Abstract: Background: Narratives can provide an interesting approach to health communication, incorporating anecdotes, imagery, and details that resonate with readers. Given this context, the purpose of this study was to explore the use of Dreamland: The True Tale of America's Opiate Epidemic to define and demonstrate an understanding of Ethos, Pathos and Logos. Methods: This qualitative, cross-sectional education research was based on the use of Dreamland: The True Tale of America's Opiate Epidemic by Sam Quinones in an undergraduate elective. The elective course focused on using popular literature to promote a better understanding of health concepts. The assignment focused on the applicability of models of persuasion (Ethos, Pathos, and Logos) used in this book. Responses ( n = 18) were compiled and reviewed following the basic premise of the Grounded Theory approach. This allowed for the identification and development of overarching themes in a way that gives a sense of how students applied this reading to the aforementioned directed question regarding models of persuasion. Results: In establishing Ethos, the author's background as a journalist and the detailed interviews with credible sources were two major themes. Student quotations demonstrate that Pathos in this book was exemplified by presenting many different aspects of a complicated epidemic, rife with possibilities for evoking emotion. Illustrative quotations indicate that students are critically analyzing the text. Conclusion: Narratives can serve as a vehicle that influences people's understandings and beliefs, potentially promoting change in behavior or attitudes. They can enhance public health education and learning in an enriching and cross-disciplinary way.